Yield and morphological performance of five Malaysian rice varieties in eight different planting densities - Mohd Rawi @ Muhammad, Raba'a (2015)
Rice as staple food for the most worldwide population provides nutrition to human. Total production of rice in Malaysia is 2.75 million tonnes in 0.68 million hectares of area cultivated. Total production of rice in Malaysia is only about 62.4% of self suffiency level (SSL). However, Malaysia needs to achieve the SSL on 2020 by 70%. The objectives of this study were to determine the optimum planting density for five Malaysian rice varieties and the effects of planting densities on yield and morphological characteristics of rice varieties. Five Malaysian rice varieties are MR 219, MR 220, MR 253, MR 263 and MR269 were planted in eight planting densities with spacing of D1 (15 cm X 20 cm), D2 (15 cm X 25 cm), D3 (20 cm X 20 cm), D4 (15 cm X 30 cm), D5 (20 cm X 25 cm), D6 (20 cm X 30 cm), D7 (25 cm X 25 cm) and D8 (25 cm X 30 cm). This experiment was laid out in a split plot design, where density was assigned as main plot and variety was assigned as sub-plot with three replications. Seedlings with fifteen day-old were transplanted in the Field 10 on March 7, 2014 with single plant per planting point. Eleven data on yield and morphological traits recorded. Analysis of variance indicated significant differences between densities and varieties in all traits except for tillers number among varieties. Present of densities X varieties interaction for the panicle length while the remaining traits were absent. Density D2 found as the optimum planting density that produced the highest grain yield.